Admissions to Hospital due to Drugs. Issue 5643 (1st March 1969) - Hurwitz, Natalie
Abstract : In a survey of adverse drug reactions in wards of two Belfast hospitals for 52 weeks in 1965–6, 2·9% of 1, 268 patients seen were admitted to hospital because of adverse reactions to drugs taken for therapeutic reasons and 2·1% were admitted because of self-poisoning. Patients admitted because of adverse drug reactions were older than those admitted because of self-poisoning and stayed in hospital longer. Among the drugs which caused the adverse reactions were digitalis preparations, antibiotics, corticosteroids, anticoagulants, analgesics, and tranquillizers. Hypersensitivity and side-effect types of reactions were the most common. Barbiturates were the most frequently used drugs in suicidal attempts.